Protective Effect of Chitosan Oligosaccharides Against Cyclophosphamide‐Induced Immunosuppression and Irradiation Injury in Mice. Issue 2 (19th January 2018) - Zhai, Xingchen; Yang, Xin; Zou, Pan; Shao, Yong; Yuan, Shoujun; Abd El‐Aty, A. M.; Wang, Jing
Abstract : Abstract: Chitosan oligosaccharides (COS), hydrolyzed products of chitosan, was found to display various biological activities. Herein, we assessed the immunostimulatory activity of COS both in in vitro and in vivo studies. In vitro cytotoxicity studies to murine macrophage RAW264.7 revealed that COS is safe even at the maximum tested concentration of 1000 μg/mL. It also stimulates the production of nitric oxide (NO) and tumor necrosis factor (TNF‐α) and enhances the phagocytosis in COS‐stimulated RAW264.7. We have shown that the COS could significantly ( P < 0.05) restore the reduced immune organs indices, phagocytic index, lymphocyte proliferation, natural killer cell activity, and antioxidant enzyme activities in a cyclophosphamide‐induced immunosuppressed mice model. COS can also improve the survival rate in irradiation injury mice and significantly ( P < 0.05) increased the spleen indices and up‐regulates the CD4+/CD8+ ratio in splenocytes. In sum, the aforementioned results suggest that COS might has the potential to be used as an immunostimulatory agent in patients with immune dysfunctions or be a model for functional food development. Practical Application: COS might has the potential to be used as an immunostimulatory agent in patients with immune dysfunctions or be a model for functional food development.